The Cod and the Cut: Intra-Active Intuitions - Hertz, Tilman; Mancilla Garcia, Maria (Frontiers in Sociology, 2021)
Interest in causality is growing in sustainability science and it has been argued that a multiplicity of approaches is needed to account for the complexities of social-ecological dynamics. However, many of these approaches operate within perspectives that establish a separation between what has causal agency and all the rest, which is relegated to the role of background conditions. We argue that the distinction between causal elements and background conditions is by no means a necessary one, and that the causal agency of background conditions is worthy of investigation. We argue that such conditions correspond to what Karen Barad has called a “cut”: a specific determination of the world (or part of it) respective to another part, for which it becomes intelligible. In this sense, most approaches to causality operate from “within” particular cuts. To illustrate this, we focus on the paradigmatic case of the Baltic cod collapse in the eighties. This case has been extensively studied overfishing has been identified as a key cause explaining the collapse. We dig deeper into the conditions which characterized fishing practices in the run-up to the collapse and uncover the separation between the social and the ecological that they enforce, by encouraging policies to increase productivity under the rationale of national development. We then re-examine the case from a process-relational perspective, rejecting the separation of nature from society. A process-relational perspective allows us to consider relations as constitutive of processes through which what exists becomes determinate. For this purpose we use the concepts of intra-action (co-constitution of processes) and of performativity (determination of language and matter within processes). We complete our conceptual framework by drawing inspiration from pragmatist philosophers and suggest that the concept of intuition can constitute an alternative to untangle causal dynamics and explain social-ecological phenomena beyond the cause/condition dichotomy. This article seeks to fulfil two objectives: firstly, to question the thick boundaries between conditions and causal elements that explain the processes in which social-ecological systems evolve; secondly, to provide a different approach to transforming a social-ecological system.